Efficient preparation method of diamond anti-reflection type periodic surface structure

By using femtosecond laser ray spots shaped by cylindrical lenses to prepare diamond periodic surface structures and using low energy defocus lasers to remove debris, the problems of low uniformity and fidelity during the preparation process are solved, and efficient preparation and optical performance improvement of large-area diamond periodic surface structures are achieved.

CN119589130APending Publication Date: 2025-03-11河北工业大学创新研究院(石家庄) +1

Patent Information

Application Number
CN202411977369.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently prepare a large-area diamond periodic surface structure, and there are problems of low uniformity and fidelity during the preparation process, which limits its functional development.

Method used

Femtosecond laser ray spots shaped by cylindrical lens are efficiently prepared. After the preliminary processing of the periodic surface structure of large-area diamonds, a secondary scan is performed using low-energy defocus laser to remove debris and improve fidelity.

Benefits of technology

The fidelity of the diamond periodic surface structure is significantly improved, its anti-reflection performance is enhanced, and optical transmittance is improved in the visible light band and the reflectivity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119589130A_ABST
    Figure CN119589130A_ABST
Patent Text Reader

Abstract

The invention provides an efficient preparation method of a diamond anti-reflection type periodic surface structure, belongs to the technical field of optical material preparation, and aims to solve the technical problems of low preparation efficiency, uniformity and fidelity of the diamond surface periodic surface structure. The preparation method of the periodic surface structure comprises the following steps that femtosecond laser passes through a cylindrical lens and an objective lens and then is converted into linear light spots, the linear light spots are focused on the surface of a diamond sample, and the linear light spots move on the surface of the diamond sample to prepare the periodic surface structure; and performing laser cleaning on the periodic surface structure. According to the method, the large-area high-uniformity diamond periodic surface structure is efficiently prepared by adopting femtosecond laser linear light spots shaped by the cylindrical lens. The low-energy out-of-focus laser is used for conducting secondary scanning on the machining area so as to remove fragments generated in the machining process, the fidelity of the periodic surface structure is remarkably improved, and therefore the obvious anti-reflection performance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical material preparation, and in particular relates to the preparation of a diamond periodic surface structure. Background Art

[0002] When the irradiation intensity of ultrafast laser approaches the material threshold, it can induce a surface structure with a period much smaller than the wavelength on the surface of the material, which is called laser-induced periodic surface structure (LIPSS). This phenomenon exists in almost any ultrafast laser irradiation. As a simple and efficient surface texturing technology, laser-induced periodic surface structure has been used to regulate material properties such as optics, electricity, and friction, and to achieve various applications such as wettability regulation, bionic surfaces and biosensors, industrial anti-icing, and micro-optics. For example, Patent Publication No. CN111168233A discloses a method for picosecond laser-induced periodic structure on the surface of optical glass, specifically: a picosecond laser beam is focused on the surface of the optical glass through a beam expansion and focusing device, and after 1-20 pulses, LIPSS is formed on the surface. The prepared LIPSS can change the optical properties of the glass, reduce the surface reflectivity and increase the transmittance.

[0003] Diamond has the characteristics of high refractive index, high breakdown electric field, and high thermal conductivity. The periodic surface structure based on diamond has important applications in optoelectronic devices, material surface treatment and other fields. In recent years, studies have shown that the optical properties of diamond can be changed by femtosecond laser-induced LIPSS. Mastellone et al. used two time-delayed and cross-polarized femtosecond laser pulses to prepare a two-dimensional periodic surface structure with a period of 80nm on the diamond surface. This structure significantly improved the light capture ability of diamond and can increase the visible light absorption rate by 50 times. In addition, as a special one-dimensional grating structure, the periodic surface structure can play an anti-reflective role on the incident light. Inspired by the moth-eye anti-reflective coating, Martinez prepared periodic surface structures with different periods and aspect ratios on the diamond surface. After simulation calculation, the periodic surface structure with a period of 500nm and an aspect ratio of 0.4 can reach 99% of the incident light transmittance. However, the periodic surface structure involved in the above research is small in area and has low preparation efficiency, which cannot meet practical applications. How to efficiently prepare large-area diamond periodic surface structures is a major challenge.

[0004] Patent publication number CN 107498183 A discloses a method for preparing a large-area periodic structure by inducing a line spot. First, a functional film material is sputtered on a glass substrate; then the glass substrate is fixed on a three-coordinate workbench, and the three-coordinate workbench cooperates with the processing optical path system; first, the output laser wavelength, repetition rate, and pulse width of the femtosecond laser are adjusted, the aperture is adjusted through a small aperture, the laser power is adjusted through an attenuation plate, and the processing process is controlled by a shutter, and then the beam is focused into a line spot through a focusing cylindrical lens; the functional film material is irradiated with the adjusted femtosecond laser, the horizontal X-direction movement speed of the three-coordinate workbench is set, and after reaching the set position, it returns to the processing starting point, moves horizontally in the Y direction, and then moves in the X-direction parallel direction, and so on and so forth, and the processing path is a series of parallel line segments, thereby producing a uniform large-area periodic structure; the patented laser is focused into a line spot through a focusing cylindrical mirror, which reduces the ablation damage to the functional film material and improves the processing efficiency. At present, although it is disclosed that a large-area periodic structure can be prepared by using a line spot, the substrates acted on are mostly glass, semiconductor materials, and alloy materials. There are few studies on the rapid preparation of periodic surface structures on the harder diamond surface, and the effect of changes in periodic surface structures on their transmittance is relatively complex. In particular, for diamond materials for optical windows with high transmittance requirements, it is still difficult to prepare them quickly and on a large scale. In addition, the applicant's research found that when preparing periodic surface structures on diamond surfaces, when the area of ​​the periodic surface structure is large, there are problems of low uniformity and fidelity, which seriously limits the functional development of diamond periodic surface structures. Summary of the invention

[0005] In view of the technical problems of low preparation efficiency, uniformity and fidelity of diamond surface periodic surface structure, the present invention proposes an efficient preparation method of diamond anti-reflection type periodic surface structure. The present invention uses a femtosecond laser line spot shaped by a cylindrical lens to efficiently prepare a large area of ​​high uniformity diamond periodic surface structure. The processing area is scanned twice by a low-energy defocused laser to remove the debris generated during the processing process, which significantly improves the fidelity of the periodic surface structure, thereby showing obvious anti-reflection performance.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0008] (1) The femtosecond laser is converted into a line spot after passing through a cylindrical lens and an objective lens and is focused on the surface of the diamond sample. The line spot moves on the surface of the diamond sample to prepare a periodic surface structure;

[0009] (2) Laser cleaning of the periodic surface structure.

[0010] The wavelength of the femtosecond laser is 400-1200nm, the repetition frequency is 10-50kHz, and the pulse width is 50-500fs.

[0011] The wavelength of the femtosecond laser is 515 nm, the repetition frequency is 25 kHz, and the pulse width is 390 fs.

[0012] The focal length of the cylindrical lens is 10-15 cm.

[0013] The numerical aperture of the objective lens is 0.7, and the magnification of the objective lens is 60 times.

[0014] The length of the line spot is 20-25 μm.

[0015] The power of the line spot is 3-6 mW, and the exposure time is 500-1000 μs.

[0016] The laser cleaning is to shape the femtosecond laser beam into an elliptical spot, and focus the elliptical spot on the surface of the microstructure for laser cleaning.

[0017] The major axis of the elliptical light spot is 15-25 μm, and the minor axis is 3-5 μm.

[0018] The focus of the elliptical light spot is located 1-3 microns above the diamond surface, the laser power is 18-20 mW, and the exposure time is 500-1000 μs.

[0019] Beneficial effects of the invention: The applicant has found that large-area diamond periodic surface structures are covered with a large amount of debris during the preparation process, which makes it difficult to prepare periodic surface structures with high uniformity and high fidelity. Therefore, the invention uses a low-energy defocused laser to perform a secondary scan on the processing area to remove the debris generated during the processing, which significantly improves the fidelity of the periodic surface structure, thereby showing obvious anti-reflection performance. The method of the invention can prepare a diamond periodic surface structure with an area of ​​12*24μm in just 3 seconds. 2 The diamond periodic surface structure can significantly increase the optical transmittance of diamond in the visible light band. The intrinsic transmittance of diamond is about 66%, while the transmittance of the diamond substrate with a periodic surface structure in the visible light band of 625nm-750nm reaches 76%, an increase of up to 10%; the reflectivity is 24%, a decrease of 10%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is the transmittance curve of diamond with a periodic surface structure.

[0022] Figure 2 This is the reflectivity curve of diamond with a periodic surface structure.

[0023] Figure 3 This is a scanning electron microscope image of the periodic surface structure of diamond. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0027] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0028] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 15 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 25 μm. The laser power was 4 mW and the exposure time was 1000 μs.

[0029] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 1 micron above the diamond surface, the laser power was 20 mW, and the exposure time was 500 μs.

[0030] (4) Diamond surface reprocessing: After laser processing, the diamond surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, and then dried in an oven and cooled to 25°C to obtain a diamond with a periodic surface structure. The structure is as follows: Figure 3 shown.

[0031] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. The femtosecond laser outputs 800nm ​​red light, which outputs supercontinuum white light after passing through the attenuator, lens and sapphire crystal, and is focused on the surface of diamond crystal through a microscope. Then, the optical transmittance and reflectivity of the sample in the 450nm-750nm band can be measured by the connected spectrometer. Figure 1 and Figure 2 The black line in the middle represents the transmittance and reflectance of the diamond body surface in the unprocessed area, and the red and blue curves represent the transmittance and reflectance of the diamond surface with a periodic surface structure. In the incident light band between 600nm and 750nm, the transmittance of the diamond crystal with a periodic surface structure increases significantly, and the reflectance decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of the diamond LIPSS structure reaches 76%, which is 10% higher than the intrinsic surface of the diamond.

[0032] Example 2

[0033] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0034] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0035] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 15 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 25 μm. The laser power was 5 mW and the exposure time was 1000 μs.

[0036] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 1 micron above the diamond surface, the laser power was 20 mW, and the exposure time was 500 μs.

[0037] (4) Diamond surface reprocessing: After laser processing, the surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, dried in an oven, and cooled to 25°C to obtain a diamond with a periodic surface structure.

[0038] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. In the incident light band between 600nm and 750nm, the transmittance of diamond crystal with periodic surface structure increases significantly, and the reflectivity decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of diamond LIPSS structure reaches 74%, which is 8% higher than that of diamond intrinsic surface.

[0039] Example 3

[0040] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0041] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0042] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 15 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 25 μm. The laser power was 6 mW and the exposure time was 1000 μs.

[0043] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 1 micron above the diamond surface, the laser power was 20 mW, and the exposure time was 500 μs.

[0044] (4) Diamond surface reprocessing: After laser processing, the surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, dried in an oven, and cooled to 25°C to obtain a diamond with a periodic surface structure.

[0045] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. In the incident light band between 600nm-750nm, the transmittance of diamond crystal with periodic surface structure increases significantly, and the reflectivity decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of diamond LIPSS structure reaches 73%, which is 7% higher than that of diamond intrinsic surface.

[0046] Example 4

[0047] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0048] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0049] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 15 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 25 μm. The laser power was 4 mW and the exposure time was 500 μs.

[0050] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 1 micron above the diamond surface, the laser power was 20 mW, and the exposure time was 500 μs.

[0051] (4) Diamond surface reprocessing: After laser processing, the surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, dried in an oven, and cooled to 25°C to obtain a diamond with a periodic surface structure.

[0052] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. In the incident light band between 600nm and 750nm, the transmittance of diamond crystal with periodic surface structure increases significantly, and the reflectivity decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of diamond LIPSS structure reaches 72%, which is 6% higher than that of diamond intrinsic surface.

[0053] Example 5

[0054] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0055] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0056] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 15 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 25 μm. The laser power was 5 mW and the exposure time was 900 μs.

[0057] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 3 microns above the diamond surface, the laser power was 18 mW, and the exposure time was 1000 μs.

[0058] (4) Diamond surface reprocessing: After laser processing, the surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, dried in an oven, and cooled to 25°C to obtain a diamond with a periodic surface structure.

[0059] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. In the incident light band between 600nm and 750nm, the transmittance of diamond crystal with periodic surface structure increases significantly, and the reflectivity decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of diamond LIPSS structure reaches 74%, which is 8% higher than that of diamond intrinsic surface.

[0060] Example 6

[0061] An efficient preparation method of a diamond anti-reflection type periodic surface structure comprises the following steps:

[0062] (1) Diamond surface treatment: The double-sided polished diamond substrate was ultrasonically cleaned for 15 minutes using alcohol and deionized water respectively, and then dried in an oven and cooled to 25°C.

[0063] (2) Preliminary processing of diamond periodic surface structure: A femtosecond laser with a wavelength of 515 nm, a repetition frequency of 25 kHz, and a pulse width of 390 fs was focused on the surface of the diamond sample through a cylindrical lens (focal length of 10 cm) and an objective lens (60×) with a numerical aperture of 0.7, and the obtained line spot length was 20 μm. The laser power was 4 mW and the exposure time was 1000 μs.

[0064] (3) Re-scanning of diamond periodic surface structure: A second laser scan was performed using an elliptical spot focused on the periodic structure surface to remove debris generated during the initial laser processing. The laser focus was located 3 microns above the diamond surface, the laser power was 20 mW, and the exposure time was 500 μs.

[0065] (4) Diamond surface reprocessing: After laser processing, the surface was ultrasonically cleaned with acetone, alcohol and deionized water for 15 minutes respectively, dried in an oven, and cooled to 25°C to obtain a diamond with a periodic surface structure.

[0066] The optical transmittance of diamond with periodic surface structure is measured by supercontinuum white light absorption spectrum. In the incident light band between 600nm-750nm, the transmittance of diamond crystal with periodic surface structure increases significantly, and the reflectivity decreases significantly. When the incident light wavelength is 750nm, the optical transmittance of diamond LIPSS structure reaches 73%, which is 7% higher than that of diamond intrinsic surface.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An efficient preparation method of a diamond anti-reflection type periodic surface structure, characterized in that: The following steps are involved: (1) The femtosecond laser is converted into a line spot after passing through a cylindrical lens and an objective lens and is focused on the surface of the diamond sample. The line spot moves on the surface of the diamond sample to prepare a periodic surface structure; (2) Laser cleaning of the periodic surface structure.

2. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 1, characterized in that: The wavelength of the femtosecond laser is 400-1200nm, the repetition frequency is 10-50kHz, and the pulse width is 50-500fs.

3. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 2, characterized in that: The wavelength of the femtosecond laser is 515 nm, the repetition frequency is 25 kHz, and the pulse width is 390 fs.

4. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 3, characterized in that: The focal length of the cylindrical lens is 10-15 cm.

5. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 4, characterized in that: The numerical aperture of the objective lens is 0.7, and the magnification of the objective lens is 60 times.

6. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 5, characterized in that: The length of the line spot is 20-25 μm.

7. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to any one of claims 1 to 6, characterized in that: The power of the line spot is 3-6 mW, and the exposure time is 500-1000 μs.

8. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 7, characterized in that: The laser cleaning is to shape the femtosecond laser beam into an elliptical spot, and focus the elliptical spot on the surface of the microstructure for laser cleaning.

9. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 8, characterized in that: The major axis of the elliptical light spot is 15-25 μm, and the minor axis is 3-5 μm.

10. The efficient preparation method of the diamond anti-reflection type periodic surface structure according to claim 9, characterized in that: The focus of the elliptical light spot is located 1-3 microns above the diamond surface, the laser power is 18-20 mW, and the exposure time is 500-1000 μs.

Citation Information

Patent Citations

  • Method for preparing large-area periodic structure through linear light spot induction

    CN107498183A

  • Method for inducing periodic structure on surface of optical glass by picosecond laser

    CN111168233A

Cited By

  • Efficient preparation method of silicon carbide anti-reflection type periodic surface structure

    CN121085664A